2019
DOI: 10.1002/ps.5436
|View full text |Cite
|
Sign up to set email alerts
|

Cool storage of Queensland fruit fly pupae for improved management of mass production schedules

Abstract: BACKGROUND Cool storage is a valuable means of manipulating insect development time. The Queensland fruit fly (Q‐fly) is Australia's most economically significant pest of fruit crops. The present study investigates cool storage of Q‐fly pupae for increasing production flexibility for sterile insect technique programs. Development time, survival and fly quality were assessed following continuous storage of 1‐day‐old pupae at temperatures ranging from 13 to 25 °C. RESULTS Survival was reduced almost to zero by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…The essence of cold storage is to utilize a sub-optimum temperature to prolong the developmental time of a bioagent whilst maintaining its quality and effectiveness against a pest [ 23 ]. Cold storage protocols are extremely valuable for inundative biological control, given that they require large-scale production and the release of huge numbers of bioagents.…”
Section: Discussionmentioning
confidence: 99%
“…The essence of cold storage is to utilize a sub-optimum temperature to prolong the developmental time of a bioagent whilst maintaining its quality and effectiveness against a pest [ 23 ]. Cold storage protocols are extremely valuable for inundative biological control, given that they require large-scale production and the release of huge numbers of bioagents.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, storage at 4.5 °C is the best option among the conditions that have currently been evaluated. Cold storage is a technique used to increase insect shelf-life in mass rearing systems [ 93 , 94 , 95 ] and, provided this does not adversely affect subsequent performance [ 92 ], allows individuals to be kept until needed in the laboratory [ 96 , 97 ] or in the field [ 98 , 99 ], thus synchronizing artificial production and release with both the culture of the laboratory hosts and the population dynamics of the target pest [ 92 , 100 , 101 ]. Despite the advantages of cold storage, there may be some negative effects such as increased mortality caused by physical or metabolic injuries (e.g., osmotic stress or anoxia) or reduced quality due to reduction or elimination of endosymbiont bacterial populations or effects on mobility, responses to chemical cues, learning capacity, fecundity, and offspring sex ratio [ 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five climatic incubators (PRX-25013, Safu, Ningbo, China) set at the specified temperature, 75 ± 5% RH and 0:24 (L:D) h photoperiod, were used to store the pupae. Emerged adults were then categorized by the following standards: (1) normal adult (fully emerged adult with normal morphology), (2) deformed adult (fully emerged adult with abnormal morphology, such as curly wings), (3) partially emerged (adult stuck in puparium until death), and (4) not emerged [21]. Normal adults and deformed adults were counted and collected from the dishes on the day of eclosion.…”
Section: Experiments 1: Effect Of Pupal Cold Storage On Developmental Parametersmentioning
confidence: 99%
“…In tephritids, several studies have been carried out to evaluate the effect of low temperature on the pupal development and the sublethal effects of extended cold storage on adult fitness traits of several economically important species to improve the flexibility and efficiency of the mass rearing programs. In terms of the effects of cold storage on the pupal development parameters, in the cases of Bactrocera oleae (Rossi) (Diptera: Tephritidae), B. tryoni (Froggatt) and Anastrepha obliqua (Macquart) (Diptera: Tephritidae), it has been shown that the extension in pupal development duration and the reduction in emergence rate were generally proportional to the decrease in storage temperature [19][20][21]. Previous work in our laboratory has shown that when three-day-old pupae of B. dorsalis (GSS) were stored at 13 • C and 16 • C for 10 or 15 days, the emergence rates were higher than 80% [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation